Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward and Peppard di Pengadilan Negeri Salatiga Kelas 1B - Deniek Gus Wijaya; Augie David Manuputty (APTIKOM SUMSEL, 2021)
The Salatiga District Court Class 1B is a legal institution. Salatiga state courts used information systems in their business processes. The existence of an information system is a powerful weapon or tool in increasing the efficiency and effectiveness of business processes in agencies. However, the IS / IT in the Salatiga District Court has not worked optimally which causes the performance to be less effective so that it requires proper IS / IT strategic planning. This study uses the Ward and Peppard method with SWOT analysis techniques. The value chain will produce information system strategy recommendations for internal and external environmental analysis, and information system application recommendation. The purpose of this research is to provide recommendations for IS / IT-related problems through strategic planning of information systems to identify IS / IT in the Salatiga District Court and to analyze IS / IT that can be used in the future to achieve an effective and efficient performance.